Health Tourism Development: An Insightful Analysis of Iran's Opportunities - Najafipour, Amir Abbas; Foroozanfar, Mohammad Hossein; Haghighat Ghahfarokhi, Farzaneh; Heidari, Majid (Journal of Foresight and Health Governance, 2025)
Health tourism is a dynamic global phenomenon; however, notable knowledge gaps remain concerning its development in emerging nations characterized by unique geopolitical and economic contexts. This research investigates the development of health tourism in Iran through a qualitative methodology, employing semi-structured interviews with 23 experts, comprising 9 healthcare providers, 8 tourism facilitators, and 6 representatives from regulatory bodies. We employed Braun and Clarke's six-step framework for thematic analysis. The findings revealed three primary themes derived from the 45 codes: (1) strategic positioning considerations, which include healthcare service excellence, cost advantage, and destination appeal; (2) operational challenges and solutions, addressing regulatory barriers, service delivery gaps, and marketing and reputation management; and (3) imperatives of innovation and sustainability, including technology integration, ecosystem development, and quality and sustainability frameworks. Iran exhibits considerable potential due to its specialized medical expertise and competitive pricing, notwithstanding the challenges posed by international sanctions and prevailing perception issues. The integrated framework of the study demonstrates the interrelationships among these dimensions, enhancing both theoretical comprehension of emerging destination development and practical implementation strategies. Future research should integrate quantitative methods, undertake longitudinal studies to assess the impacts of technological innovation, conduct comparative analyses with regional competitors, and explore outcomes that prioritize patients from the perspectives of international health tourists. This analysis examines the interplay between geopolitical constraints and healthcare service delivery, providing insights for stakeholders in healthcare, tourism, and regulatory sectors.